Photocatalytic Degradation of Organic Dyes under Visible Light on N-Doped TiO2 Photocatalysts - Olga Sacco; Marco Stoller; Vincenzo Vaiano; Paolo Ciambelli; Angelo Chianese; Diana Sannino (International Journal of Photoenergy)
This study was focused on the application of white and blue light emitting diodes (LEDs) as sources for the photocatalytic degradation of organic dyes in liquid phase with visible light. The photocatalytic activity of N-doped titanium dioxide, synthesized by direct hydrolysis of titanium tetraisopropoxide with ammonia, was evaluated by means of a batch photoreactor. The bandgap energy of titanium dioxide was moved in the visible range from 3.3 eV to 2.5 eV. The visible light responsive photocatalysts showed remarkably effective activity in decolorization process and in the removal of total organic carbon. Methylene blue was also used as a model dye to study the influence of several parameters such as catalyst weight and initial concentration. The effect of dye on the photocatalytic performance was verified with methyl orange (MO). The results demonstrated that the right selection of operating conditions allows to effectively degrade different dyes with the N-doped TiO2 photocatalysts irradiated with visible light emitted by LEDs.